Legislative controls on Islamic banking in Algeria: a review of regulations 18-02 and 20-02. - raouane, abdelrahmanne; yagoub, larbi (Journal of Research in Finance and Accounting, 2025)
Like other legal systems that have fully or partially adopted Islamic banking in their operations, the Algerian legislator has sought to establish legal frameworks that take into account the specificities and principles of Islamic banking. As part of this effort, certain legislative systems have been introduced that outwardly reflect the particularities of Islamic banking practices. Among the economic reforms that have supported Islamic banking is Regulations 18-02 and 20-02. Hence, this study is entitled: "The Legislative Framework for Islamic Banking in Algeria: An Analysis of Regulations 18-02 and 20-02.".